Zooloween - Katz, Alan; Laberis, Steph (New York, NY Harper, 2024)
"It's Halloween at the zoo, and it's time for the animals to show off their costumes! But who will win the grand prize for best dressed? The night is full of fun and surprises!"--
114288
Keywords: Halloween -- Juvenile fiction; Halloween costumes -- Juvenile fiction; Zoo animals -- Juvenile fiction; Zoos -- Juvenile fiction; Animal fiction; Picture books